Technical openness in the formation of postmodernism Pop Art Example (An analytical study) (Al-Academy, 2016)
Addressed the problem of the research is marked (technical openness in the formation of post-modernism - Pop Art an Example) the nature of the technical expansion of the output artifacts postmodern, and the nature of the raw materials taken as components of its sensual. The search came in four sections: general framework for research and identified the research problem and the need for him. With an indication of the importance of his presence. From then select the search goal (revealed openness to hire technical material in the art of Pop Art), followed by the establishment of the three search limits (objectivity, the temporal and spatial) were then determine the terms related to the title. Then provide the theoretical framework and indicators that resulted from academic theorizing of the subject. The researcher has identified three addresses implied within this framework to ensure reading placed search according to the various frameworks tariff. Were as follows: technical introductions openness in modern art/ intellectual hypothalamus of the contemporary artist/ art Pop Art: Growing concept. The third chapter is devoted to the research procedures, through the detection studied society and the selected sample of it (4works) and then specify the search tool and determine the methodology, followed by an analysis of the sample. The fourth chapter included the search results, including:1. Detection model (1) that the technique does not rely solely on the components of the artwork, but extends to include support vocabulary as a verb exterior lighting and the shadows on the wall and the ground, as well as artwork.2. Foot model (2) and sensory broker subject for human consumption and engage then as technical supply the material composition developed, represented by empty cans that line up vertically in the middle of the artwork.3. View the artist's model (3) face another technique the formation of post - modernism, like the style of printing Professional (Silk screen) to contain details of a mock life for consumers of contemporary society.4. Detection model (4) for the machine in aid implementation clearly, away from pure manual capabilities, as in the business developed from the sample (models 1, 2, 3), which adopted the role of the manual.